(untitled) (Annual of the Faculty of Philosophy in Skopje, 2021)
The genitive singular forms of the thematic declension in Mycenaean Greek usually end in -oio. In the postmycenaean period *-osyo, apart from the epic poetry and later poetic reminiscences of the Homeric poems as a regular ending is found only in the Thessalian dialect. However, the comparison of the Mycenaean and Thessalian examples shows differences in the use of *- osyo both on morphological and syntactical level, i.e. it points to a formulaic and limited use of this ending in Thessaly opposite to its lively and unlimited use on the Mycenaean tablets.